Karyotypic Analysis of four Species of Genus Blumea (Asteraceae) from Nepal - Karna Mallick, Pushpa (International Journal of Applied Sciences and Biotechnology, 2018)
In this study chromosome number determination and karyotype analysis of four species of genus Blumea from the family asteraceae was carried out. The specimen plants were collected from central parts of Nepal, namely Blumea fistulosa (Roxb.) Kurz, Blumea lacera var.glandulosa (DC.) Hook, Blumea lacera (Buem f.) DC. and Blumea laciniata DC were observed. The chromosome number in somatic cells were recorded to be 2n= 22 in Blumea fistulosa; 2n= 32 in Blumea lacera var.glandulosa; 2n=18 in Blumea lacera and Blumea laciniata. The range of chromosome length found to be 0.6 to 1.6 µm in Blumea fistulosa, 0.6 to 1.6µm in Blumea lacera var.glandulosa, 0.6 to 1.7 µm in Blumea lacera and 0.8 to 1.6 µm in Blumea laciniata. Karyotype formula for Blumea fistulosa is M12+ sm10, for Blumea lacera var. glandulosa is M14+sm14+ st4, for Blumea lacera is M14+ st2 and for Blumea laciniata is M12+ sm6 in Blumea laciniata. In this investigation a pair of satellite chromosome found in only one species Blumea fistulosa at the end of shot arm of chromosome. Mainly three types of chromosomes observed in this study having centromere at middle point, at sub-median region and at sub-terminal region. Numerical and structural variation in chromosome are evolutionary significance. Similarity in size of chromosomes and karyomorphology indicates the homogeneity of the taxa within this tribe. Int. J. Appl. Sci. Biotechnol. Vol 6(2): 115-121